School Management as a Factor for Effectiveness and Change: A shift in Chile's School Managment - Sergio Garay O.; Mario Uribe (Universidad Autónoma de Madrid, 2018)
This paper analyzes the School management in the Chilean reality, offering, in the first place, a panoramic vision of the context in which it develops, a revision of the public policies of the last years and the implementation of the reform; in addition, we have wanted to investigate in the studies of school effectiveness in this reality and the contributions reached from its vision. We could not finish this work without offering some conclusions, that they tend to be challenges or pending tasks so that the "School management" has possibilities of being a real factor of effectiveness and change in our schoool system.